Applications of information support technologies for small and medium enterprises: a research agenda. (19th April 2004) - Ngai, E.W.T.; Cheng, T.C.E.
This paper presents a research agenda for applying information support technologies (ISTs) in small and medium enterprises (SMEs), including two research frameworks to guide investigations into the way in which SMEs can benefit from applying ISTs in their operations. First, we discuss the potential of applying management support systems (MSS) for quality improvement in the context of business process re-engineering (BPR) and suggest a viable strategy to assist in the choice of an appropriate approach to process improvement. Then, we describe the potential application of the system development approach for developing an MSS for process improvement. Finally, we discuss the application of electronic commerce for SMEs and suggest a viable approach to research in this area. We believe that applying state-of-the-art ISTs is a potent force to strengthen the capacities of SMEs to compete in the export market and ensure SMEs remain as competitive as ever in the international market. The implications of this study are highlighted.